Analysis of Consumer Satisfaction on Hydroponic Vegetables - Tsalis Kurniawan Husain; Farizah Dhaifina Amran (JURNAL MANAJEMEN AGRIBISNIS, 2022)
CV. Akar Hidroponik is a business engaged in the agricultural sector which focuses on producing and marketing hydroponic vegetable products. The trend of urban consumers in consuming healthy food makes their considerations in buying vegetables much more complex. The purpose of this study is to analyze the level of consumer satisfaction of hydroponic vegetables. The basic method used is descriptive quantitative analysis method. The sampling using purposive sampling method with 52 respondents. The respondents are consumers of CV. Akar Hidroponik who are joined as members on Whatsapp group of @akar_hidroponik. This study tested the validity and reliability using SPSS software version 20. The analytical method used was the Customer Satisfaction Index (CSI). The results showed that the level of consumer satisfaction of hydroponic vegetables based on the value of the Customer Satisfaction Index was 89.03%, which is categorized as very satisfied. The variables that gave the highest satisfaction were the nutritional content of vegetables, the benefits of vegetables, the safety and security of vegetables for consumption, and the freshness and cleanliness of the vegetables.